Peptides for the New Millennium Proceedings of the 16th American Peptide Symposium June 26Ớ<U+001c>July 1, 1999, Minneapolis, Minnesota, U.S.A. - Fields, Gregg B.; Tam, James P.; Barany, George. (American Peptide Symposia, 2002)
ỚSHave you tried peptides? Small proteins, the best in the land! WonỚ"t you try peptides? Keep all your body processes in hand! For labor and lactation oxytocin you must buy! Enkephalin always gives a good runnerỚ"s high! So wonỚ"t you try peptides? Small proteins, the best in the land!Ớ<U+00fd> The above words [1], penned by Gary Gisselman to open Peptide ©&ngst: La Triviata, the opera which made its world premiere on July 1, 1999, also serve as a fitting charge to the th 16 American Peptide Symposium. This latest edition of a premier biennial series was held under the auspices of the American Peptide Society, June 26Ớ<U+001c>July 1, 1999, at the Minneapolis Convention Center, Minneapolis,Minnesota, with the undersigned serving as Co-Chairs. The fortunate coincidence of the calendar allowed us to set as the theme ỚSPeptides for the New MillenniumỚ<U+00fd>, and in our judgment, the approximately 1200 participants [2] who converged in the Twin Cities from academic and industrial institutions in 36 countries were treated to an exciting and stimulating conference that left most everyone with an enthusiastic vision for the future of our field. The present Proceedings volume should serve as a handy reference source and succinct snapshot of peptide science at essentially its century mark Ớ<U+001c> the clock having started with the initial contributions of Emil Fischer and Th. Curtius.